The Effectiveness of Sharia Supervisory Board (DPS) Supervision on Baitul Maal Wat Tamwil (BMT) in Implementing Sharia compliance: (Case Study of Tamzis Bina Utama Kotagede) - Rani Devitasari; Syah Amelia Manggala Putri (Universitas Ahmad Dahlan, 2023)
The purpose of this study is to determine how effective the role of the Sharia Supervisory Board (DPS) is in implementing sharia compliance in the Tamzis Bina Utama Sharia Financing Savings and Loans Cooperative Kotagede Branch Office. This type of research uses a qualitative approach. Data collection methods include observation, interviews, and documentation. Data sources consist of primary data obtained directly from research sources as well as secondary data. The validity of the data is tested using source triangulation and triangulation techniques. Data reduction techniques, data presentation, and conclusions carry out data analysis. The results show that the implementation of sharia compliance by the Sharia Supervisory Board (DPS) in the supervisory mechanism at the Tamzis Bina Utama KSPPS Kotagede Branch Office is following the Standard Operating Procedures (SOP) regulated in the duties and functions of DPS, as stipulated in the MUI decision on the composition of the DSN-MUI management number Kep-98 / MUI / III / 2001. DPS is also active in providing Islamic briefing to prospective employees by holding routine activities such as cults, Riyadhus Sholihin recitations, recitations every week, Islamic economic studies every Thursday, MABIT once a month, and periodic training on contracts, as well as holding random branch office visits. Based on sharia principles stipulated in Article 2 of Law No. 21 of 2008, KSPPS Tamzis Bina Utama Kotagede Branch Office has ensured compliance with Sharia Compliance in the implementation of financing and raising funds.